The impact of individual differences on EFL English language learning --The case of Second Year University of Msila. - Sabrina Boubakeur, Saadi Nawal (My University, 2021)
Abstract This study investigated the root causes of individual differences and their impact on English language learning, knowing the students’ individual differences and taking them into consideration by teachers will help students to acquire the language better then when they don’t put them into consideration, this study examines second-year LMD students of English at the University of Mohamed Boudhiaf M'sila. This research was designed to answer the research question which is: “How could learners' individual differences affect the English language learning?” To answer this question researchers, use a descriptive analytical method. A combination of quantitative and qualitative methods is used also in data collection. Data is collected through questionnaires, the questionnaires were about students’ individual differences, and the population of this research consists of 80 LMD second year students and 10 English teachers at the University of M'sila, where 27 students will represent the sample that will be selected randomly. The preliminary results of the research show that the EFL students are not aware of the importance of their individual differences in the process of acquiring language and it will be helpful if they take it into consideration. However, due to these individual differences, EFL teachers are not aware of the students’ different needs and abilities to provide them with appropriate help and guidance.
Keywords: Keywords: Individual differences, Learning, Impact